PERSEPSI SAKIT DAN SISTEM PENGOBATAN TRADISIONAL DAN MODERN PADA ORANG AMUNGME (STUDI KASUS DI KECAMATAN ALAMA KABUPATEN MIMIKA) - Amisim, Anius; Kusen, Albert W. S.; Mamosey, Welly E. (Universitas Sam Ratulangi, 2020)
Basically everyone has the right to live prosperous living and inner, dwelling, gaining a healthy living environment and deserve health care. Healthcare services such as hospitals, clinics, health centers and others are comprehensive health services ranging from preventive, curative, promotive, and rehabilitative should be able to provide healthcare services without looking at the social status of the community.The Based on this condition, a lot of preventive and curative health life occurs based on traditional medicine system, and the treatment is there and has been utilized in local area of Amungme before they get acquainted with the modern medicine system. The traditional medicine is also referred to as alternative medicine, generally owned by the society according to their cultural patterns in the form of their original knowledge.Traditional medicine is referred to as a culture in local wisdom that exists in the Amungme peoples and according to their diversity of healthy perception and pain. Then the phenomenon of traditional medicine exists and lives in the form of knowledge, beliefs, values, norms as culture of the people with the culture of the community; And the phenomenon is in the community is confronted by the system of modern medicine medicine introduced by the Government to the citizens.People of Amungme have a source of traditional medicine such as shamans/smart people or with the term Amungme society called Moweme, Tawunamor mame and Inkupin each have the ability to heal pain with traditional treatment systems that are inherited hereditary by the ancestors of the Amungme tribes.Â Keywords: health, traditional, perception